2019
DOI: 10.2172/1506970
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of Supercritical Carbon Dioxide Technology through Round Robin Testing and Fundamental Modeling

Abstract: is a Technical Executive at Electric Power Research Institute (EPRI). EPRI provided round robin samples to all participants and served in an advisory role at meetings and workshops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…As a final note on the round robin, Table 2 shows that for the second run in this study, the measured rates for the highly alloyed materials were similar to two other institutions where the data were readily available for calculating rate constants. There was some variation in the total mass gain [15], i.e. the transient behavior, which may reflect differences in the heating rate and starting procedures as the specimen composition and surface preparation were the same for all participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a final note on the round robin, Table 2 shows that for the second run in this study, the measured rates for the highly alloyed materials were similar to two other institutions where the data were readily available for calculating rate constants. There was some variation in the total mass gain [15], i.e. the transient behavior, which may reflect differences in the heating rate and starting procedures as the specimen composition and surface preparation were the same for all participants.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens for the round-robin testing were all prepared by one organization. The four commercial alloys (measured compositions shown in Table 1 [15]) were machined into parallelepiped specimens (~19 x 19 x 2 mm) and polished to a 600-grit finish. Six specimens of each alloy were exposed in each experiment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An example of the recorded mass change data at 750 ℃ in atmospheric (1 bar) and high pressure (300 bar) sCO 2 up to 10,000h is shown in Figure 1. Tucker et al [15] summarized various data sources and reported mass change behavior of 625 and 740H in 200 bar sCO 2 and this is summarized in Figure 2. Holcomb et al [24] conducted tests in sCO 2 at 730 ℃ and 207 bar and compared measured oxidation kinetics with values in the literature.…”
Section: Corrosion Data In Scomentioning
confidence: 99%